The Mitochondria-Associated ER Membranes Are Novel Subcellular Locations Enriched for Inflammatory-Responsive MicroRNAs - Wang, Wang-Xia; Prajapati, Paresh; Nelson, Peter T.; Springer, Joe E. (Molecular neurobiology, 2020)
The mitochondria-associated endoplasmic reticulum (ER) membranes (MAMs) are specific ER domains that contact the mitochondria and function to facilitate communication between ER and mitochondria. Disruption of contact between the mitochondria and ER is associated with a variety of pathophysiological conditions including neurodegenerative diseases. Considering the many cellular functions of MAMs, we hypothesized that MAMs play an important role in regulating microRNA (miRNA) activity linked to its unique location between mitochondria and ER. Here we present new findings from human and rat brains indicating that the MAMs are subcellular sites enriched for specific miRNAs. We employed subcellular fractionation and TaqMan® RT-qPCR miRNA analysis to quantify miRNA levels in subcellular fractions isolated from male rat brains and six human brain samples. We found that MAMs contain a substantial number of miRNAs and the profile differs significantly from that of cytosolic, mitochondria, or ER. Interestingly, MAMs are particularly enriched in inflammatory-responsive miRNAs, including miR-146a, miR-142-3p, and miR-142-5p in both human and rat brains; miR-223 MAM enrichment was observed only in human brain samples. Further, mitochondrial uncoupling or traumatic brain injury in male rats resulted in the alteration of inflammatory miRNA enrichment in the isolated subcellular fractions. These observations demonstrate that miRNAs are distributed differentially in organelles and may re-distribute between organelles and the cytosol in response to cellular stress and metabolic demands.